PEMERINTAH ACEH. - Mardiati, Ilyas Ismail, Muhammad Shaleh Sjafei. (Jurnal Ilmu Hukum, 2015)
Abstract: Article 213 paragraph (2) of Law No. 11 in 2006 and in Article 2 of Decree of the President of Republic of Indonesia Number 34 Year 2003, said that the authority of the Government in response to land held by the District / City. Of the few cases that imposed to the Government of Aceh, there are still many unresolved cases. The study aims to determine the implementation of land conflict resolution by the Provincial Government of Aceh and analyze constraints in land conflict resolution by the Provincial Government of Aceh. Based on the Object problem there are 2 ( two ) studies used in this thesis , the normative legal research and empirical legal research. Reaseach findings shows that there are 33 (Thirty Three) cases of land conflict and 5 (five) cases were completely resolved by the Government of Aceh where the adjudication process performed through negotiation, mediation, customary law and the rule of law. Barriers that occur in this implementation are :( 1) Lack of awareness of the district and city / Dispute Resolution team to resolve the issue of land (2) The duality of authority settlement of land conflicts between the National Land Agency and the Government of Aceh-Indonesia; (3) The number of agencies involved in the process of handling land issues. All parties involved in conflict and other related parties in the process of completion are advised to emphasize more on consensus while it is still guided by a system of laws and regulations and the Government of Aceh optimize performance through Land Conflict Resolution Facilitation Team both at the provincial and district / city. Keywords: Land Conflicts. Abstrak: Pasal 213 ayat (2) Undang-Undang Nomor 11 Tahun 2006 dan Pasal 2 Keputusan Presiden Republik Indonesia Nomor 34 Tahun 2003 menyebutkan bahwa kewenangan Pemerintah di bidang pertanahan dilaksanakan oleh Pemerintah Kabupaten/Kota. Dari beberapa kasus yang masuk ke Pemerintahan Aceh, masih banyak kasus yang belum terselesaikan. Tujuan untuk mengetahui pelaksanaan penyelesaian konflik pertanahan oleh Pemerintah Provinsi Aceh dan menganalisis hambatan-hambatan dalam penyelesaian konflik pertanahan oleh Pemerintah Provinsi Aceh. Berdasarkan Objek masalah terdapat 2 (dua) penelitian yang digunakan dalam tesis ini, penelitian hukum normatif dan penelitian hukum empiris.Hasil Penelitian menunjukan terdapat 33 (Tiga Puluh Tiga) kasus konflik pertanahan dan 5 (lima) kasus yang selesai terselesaikan oleh Pemerintah Aceh dimana proses penyelesaiannya dilakukan melalui Negosiasi, Mediasi, Hukum Adat dan Aturan PerUndang-Undangan. Hambatan yang terjadi pada pelaksanaan ini (1) Kurangnya kepedulian pemerintah kabupaten dan kota/Tim Penyelesaian Sengketa untuk menyelesaikan persoalan pertanahan (2) Dualisme kewenangan penyelesaian Konflik pertanahan antara Badan Pertanahan Nasional-RI dan Pemerintah Aceh; (3) banyaknya instansi yang terlibat dalam proses penanganan permasalahan pertanahan. Disarankan Seluruh pihak yang berkonflik dan pihak terait lainnya dalam proses Penyelesaian lebih mengedepankan musyawarah mufakat dengan tetap mempedomani sistem peraturan perundang-undangan dan Pemerintah Aceh mengoptimalkan kinerja melalui Tim Fasilitasi Penyelesaian Konflik Pertanahan baik di Provinsi dan Kabupaten/Kota. Kata Kungci : Konflik Pertanahan.